Evaluation of the efficacy of hydrocyn™ aqua in comparison to commercially available super oxidized solution as dressing solution for diabetic foot ulcers - Aziz, Mohd Shaharil Abdul (2016)
Introduction: Diabetic patients will have a 15% of risk of developing diabetic foot ulcers during the disease course and usually this is complicated by infections. The principle aim of treatment is to promote wound healing combining surgical and non-surgical treatment. Disinfectants have been used traditionally but it has the argument of cyto-toxicity against host. Hydrocyn™ Aqua is an antiseptic solution in the form of stable super oxidized solution with neutral pH and longer shelf life which can be used in the treatment of diabetic foot ulcers. Objective: The objective of this study is to compare the efficacy of Hydrocyn™ Aqua with the commercially available super oxidized solution (CASOS) in term of wound size reduction and optimal wound bed preparation. Methodology: This was a prospective, single-blinded randomized controlled trial involving patients with diabetes mellitus, who attended Orthopaedic Department Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian between January to December 2015 which have been surgically debrided. Patients who fulfilled the criteria were randomized to receive treatment with Hydrocyn™ Aqua (n = 30) or CASOS (n = 30) with daily dressing for 2 weeks. Outcome measures include demographic data, size of wounds, wound bed scoring and complications at baseline and at 2 weeks. Results: Wound reduction percentage after 2 weeks of treatment with Hydrocyn™ Aqua and CASOS showed no difference in both groups (p= 0.9). The wound bed scoring at 2 weeks of treatment showed no difference for both treatments. (p= 0.09) There was no adverse reactions recorded for both groups. Conclusion: There is no significant difference for the efficacy of Hydrocyn™ Aqua compared to the commercially available super oxidized solution in the treatment of diabetic foot ulcers.